2021
DOI: 10.3389/fonc.2021.689136
|View full text |Cite
|
Sign up to set email alerts
|

CT Radiomics for the Preoperative Prediction of Ki67 Index in Gastrointestinal Stromal Tumors: A Multi-Center Study

Abstract: PurposeThis study established and verified a radiomics model for the preoperative prediction of the Ki67 index of gastrointestinal stromal tumors (GISTs).Materials and MethodsA total of 344 patients with GISTs from three hospitals were divided into a training set and an external validation set. The tumor region of interest was delineated based on enhanced computed-tomography (CT) images to extract radiomic features. The Boruta algorithm was used for dimensionality reduction of the features, and the random fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…After step-by-step screening, 12 features were filtered, including four wavelet transform features and seven Gaussian filter features, and only one feature was obtained from the original images. Therefore, we speculate that the wavelet transform and Gaussian filter can highlight the details in the original images and show more information, and thus can better reflect the heterogeneity between tumors, which is consistent with the conclusions of Qi et al and Zhao et al 32,37 GLCM is a type of image analysis technology that can describe the distribution and shape of image pixels in the form of a grey matrix. 38 GLRLM is the same as GLCM, which can evaluate the distributions of discrete grayscale in the images; however, GLCM evaluates gray symbiosis between adjacent pixels or voxels, and GLRLM evaluates the run length.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After step-by-step screening, 12 features were filtered, including four wavelet transform features and seven Gaussian filter features, and only one feature was obtained from the original images. Therefore, we speculate that the wavelet transform and Gaussian filter can highlight the details in the original images and show more information, and thus can better reflect the heterogeneity between tumors, which is consistent with the conclusions of Qi et al and Zhao et al 32,37 GLCM is a type of image analysis technology that can describe the distribution and shape of image pixels in the form of a grey matrix. 38 GLRLM is the same as GLCM, which can evaluate the distributions of discrete grayscale in the images; however, GLCM evaluates gray symbiosis between adjacent pixels or voxels, and GLRLM evaluates the run length.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, radiomics showed great potential for GISTs, which can effectively predict the malignant potential of GISTs, 28,29 mitotic index, 30 and Ki-67 expression index. 31,32 In addition, a preliminary study has been conducted on the use of radiomics for the classification and prediction of GISTs gene mutations. Xu et al showed that CT texture analysis is helpful in distinguishing whether GISTs have KIT exon 11 mutations on enhanced CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and colleagues have reported that patients who are receiving adjuvant therapy with more than 8% Ki67 levels may have a poorer prognosis. 30 Lopez Gordo et al also indicated a relevance between Ki67 levels and overall survival, however there it was not associated with recurrence. 18 According to National Cancer Institute (Surveillance, Epidemiology and End Results: Localized, Regional a Distant), the 5-Year overall survival rate of all stages of GISTs including all primary tumor sites is 83% (28).…”
Section: Discussionmentioning
confidence: 94%
“…In particular, Song et al 11 and Zhang et al 28 developed models based on CT scans, capable of stratifying patients between low and high risk, yielding an AUC of 0.85 and 0.94, respectively. Other studies, such as those from Zhang et al 30 and Zhao et al 29 developed radiogenomics models to evaluate Ki-67 expression, to predict disease-specific survival and risk of recurrence. Of the above, preliminary assessment of the Ki-67 expression was the most promising (AUC = 0.78 in both studies).…”
Section: Resultsmentioning
confidence: 99%